The Impact Of Distribution Management On Guinness PLC Product Availability In Calabar - Etim, Ndem Samuel; Sunday, Ezekiel Maurice; George Eni, Martin (Archives of Business Research, 2018)
This study on the impact of distribution management on the product availability of Guinness Nigeria Plc in Calabar, focuses on how operational distribution management components such as channel conflict resolution, channel motivation and order processing can be used in ensuring the availability of Guinness products among channel intermediaries in Calabar, The study adopted the descriptive and survey research design, of which data was collected from a sample size of 34 channel intermediaries which covered major distributors, wholesalers and retailers of Guinness brands in Calabar who were selected based on the simple random sampling technique of which their responses were electronically analyzed using multiple regression as a statistical tool in SPSS version 20,the overall result of the r – square of the regression model showed a significant predictability of channel conflict resolution, channel motivation, and order processing on product availability. However, order processing as an operational distribution management component had the most significant impact on the product availability of Guinness Nigeria Plc in Calabar. Thus, it was recommended that Guinness Nigeria Plc should focus more on expediting her order processing methods because it most significantly ensures the availability of a firm’s product more than conflict resolution and channel motivation variables